Primitive neuroectodermal tumour of kidney: an unusual entity - Wadhwani, Deepa; Gangwal, Kumud; Bhargava, Shilpi; Shah, Ruchit; Tejwani, Shankar; Gauba, Rajat (Annals of Pathology and Laboratory Medicine, 2015)
Primitive neuroectodermal tumor (rPNET ) of kidney is an extremely rare tumour which occurs in children and young adults and has only a few published reports. The present case is of a 24-year-old female presenting with complaining of pain abdomen since 2-3 months duration. USG guided FNAC showed a cellular aspirate composed of small round to oval cells with scanty or small amount of cytoplasm was seen. Cells were arranged in clusters with occasional microacinar or papillary arrangement was also noted. Two possibilities were suggested- 1.Carcinoid tumour, 2. small cell anaplastic carcinoma. Histopathological and immunohistochemical (IHC) correlation was done. A highly malignant small cell neoplasm composed of small round cells having scanty cytoplasm and dense nuclei against hemorrhagic background was seen. IHC panel was performed and was found to be strongly positive for MIC-2 (CD99) and showed weak positivity for NSE and ki -67. A final diagnosis of Primitive Neuro-ectodermal Tumour of kidney was made.